2005
DOI: 10.1021/jp044151q
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Nanosize Products of the Sol−Gel Reaction Using Diphenylsilanediol and 3-Methacryloxypropyltrimethoxysilane as Precursors

Abstract: We use a first-principles calculation and small-angle neutron scattering (SANS) to investigate the mechanism and the nanosize products of the sol-gel reaction with diphenylsilanediol (DPD) and 3-methacryloxypropyltrimethoxysilane (MEMO) precursors in synthesizing a hybrid waveguide material. It is predicted that switching between a DPD hydroxyl and a MEMO methoxy with a reaction rate of 6.8 x 10(-6) s(-1) at 300 K is the fastest process for the first reaction step, thus generating diphenylmethoxysilanol (DPM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 35 publications
(54 reference statements)
3
20
0
Order By: Relevance
“…In fact, pillar collapse was observed in pillars with aspect ratios > 5, in accordance with theoretical predictions. [31][32][33][34][35][36][37][38] Higher aspect ratios can be obtained by molding with harder materials, e.g., composite PDMS, [36,37,39] bilayer PDMS, [34,37,40] photocurable PDMS, [39,41] polyolefins, [42] PDMS with polymer-reinforced sidewalls, [43] fluoropolymers, [44][45][46] photocurable perfluoropolyethers, [47] photocurable fluorinated organic-inorganic hybrids [44,[48][49][50][51][52] or photocurable polyurethane acrylates. [53,54] Molding was also performed with elastomeric silicones used in the dental clinic for making denture impressions: Provil Novo, President and P2 (see Experimental part for details).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, pillar collapse was observed in pillars with aspect ratios > 5, in accordance with theoretical predictions. [31][32][33][34][35][36][37][38] Higher aspect ratios can be obtained by molding with harder materials, e.g., composite PDMS, [36,37,39] bilayer PDMS, [34,37,40] photocurable PDMS, [39,41] polyolefins, [42] PDMS with polymer-reinforced sidewalls, [43] fluoropolymers, [44][45][46] photocurable perfluoropolyethers, [47] photocurable fluorinated organic-inorganic hybrids [44,[48][49][50][51][52] or photocurable polyurethane acrylates. [53,54] Molding was also performed with elastomeric silicones used in the dental clinic for making denture impressions: Provil Novo, President and P2 (see Experimental part for details).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. b, the free radical addition reaction of the QD/oligosiloxane (methacryl) resin results in the formation of carbon single bonds by two cross‐linking reaction pathways: the one is the reaction between C═C bonds of methacryl groups of siloxane matrix (i.e., cross‐linked bonds between siloxane matrix), and another is the reaction between C═C bonds of the methacryl group and OA (i.e., cross‐linked bonds between QD and siloxane matrix) . While, the epoxy ring opening cationic reaction of the QD/oligosiloxane (epoxy) resin results in the formation of only ether bonds of between epoxy groups of siloxane matrix .…”
Section: Resultsmentioning
confidence: 99%
“…We fabricated the QD/siloxane (methacryl) film via UVinduced cross-linking of free radical addition reaction to solidify the CdSe/ZnS QDs in oligosiloxane (methacryl) resin (concentration of QDs: 0.5 wt%) which was synthesized by sol-gel condensation reaction between silane precursors of MPTS and DPSD. 22 Similarly, the QD/siloxane (epoxy) film was fabricated via UV-induced cross-linking of epoxy ring opening cationic reaction to solidify the same batch of CdSe/ZnS QDs in oligosiloxane (epoxy) resin which was synthesized by sol-gel condensation reaction between silane precursors of ECTS and DPSD. 23 Figure 1a shows traces of PL QY of QD/siloxane (methacryl) film and QD/siloxane (epoxy) film observed for 40 days of aging in air at 85°C and 5% RH for 40 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10] For the preparation of planar waveguides, photosensitive inorganic-organic hybrid films prepared by the sol-gel method have been studied extensively. [11][12][13][14][15][16][17][18][19] In these studies on inorganic-organic hybrid films, trimethoxysilylpropylmethacrylate TMSPM has been favored as a precursor since the methacrylate group easily polymerizes under UV irradiation or thermal treatment, 20 and the polymerization leads to an increase of refractive index to control waveguiding. We have reported on the preparation of inorganic-organic hybrid films from vinyltriethoxysilane VTES, allyltriethoxysilane or TMSPM, and zirconium n-tetrapropoxide modified with methacrylic acid, 21 and found that patterns with a width of about 10 mm and thickness of about 15 mm were formed by the etching of unirradiated region of the films.…”
Section: 4mentioning
confidence: 99%